(untitled) (Research, Society and Development, 2020)
The topic of Drug Education has been discussed in the area of Science Education and in policies related to public health, with an emphasis on licit drugs, such as caffeine products, present in a variety of commercialized foods. This article contextualizes the consumption of coffee and other caffeine products as psychoactive foods used by young people and adults over time. Given these aspects, based on bibliographic research, centered on the qualitative approach, the article in question aims to highlight the recent stimulus to the consumption of foods and beverages with caffeine composition as a practice influenced by the food industry - to some extent as substitutes for the compositions alcoholics -, recognizing that some practices of abstinence from such products may not be reached or desired by young people and adults of more recent generations. Thus, the article defends Harm Reduction as an attainable pedagogical perspective, believing that the pursuit of quality of life may be combined with common sense and less aggressive and abusive eating practices.